A Passivity Approach to the Stabilization of Free-Radical Polymerization Reactor - Nguyen T. Sang; Hoang N. Ha; M.A. Hussain (ASEAN Journal of Chemical Engineering, 2018)
This work proposes a tracking error passivity-based multivariable control viafeedback passivation for a class of free-radical polymerization systems in a continuouslystirred tank reactor (CSTR). Firstly, this system dynamics with high nonlinearity ispassivized by input coordinate transformations, the resulting passive system is then rewritten into a canonical form strongly related to the so-called Port Control Hamiltonianstructure. Actually, this representation allows to show the physical meanings of systemdynamics such as dissipative, non-dissipative terms and supply rate. From this, a feedbackcontroller based on tracking error is designed for the globally exponential stabilization atan arbitrarily chosen reference trajectory passing the desired equilibrium point. Thetheoretical developments are then illustrated for polystyrene polymerization system inthe CSTR. The numerical simulations show that the trajectories of styrene polymerizationsystem considered as an illustrative example of FRP system converges globallyexponentially to the imposed trajectories.